Quantitative accuracy of PET∕CT for image-based kinetic analysis - Seo, Youngho (American Association of Physicists in Medicine, 2008)
Accuracy in quantification of activity concentrations (e.g., in Bq∕ml) is essential for compartment modeling and kinetic analysis of dynamic reconstructed PET images. Dynamic PET data can be acquired in list-mode, and often are preferred over frame mode acquisitions due to the flexibility of reformatting the list-mode data into different dynamic image sequences after the acquisition is complete. However, most PET data are acquired as static frames. It therefore is important to evaluate the quantitative accuracy of list-mode or dynamic PET acquisitions prior to their use for clinical or research applications. The quantitative accuracy of list-mode acquisitions obtained with a Siemens Biograph 16 PET∕CT scanner at our institution was evaluated; the image data were acquired from an anthropomorphic phantom (Data Spectrum, Hillsborough, NC) filled with an aqueous solution of (18)F-fluorodeoxyglucose (FDG). PET data were acquired with the phantom for the following three different configurations: (1) with nonradioactive water in the body compartment and aqueous solution of (18)F-FDG in only a fillable cylindrical insert to simulate the first several seconds of highly concentrated radioactivity within the field of view such as that in major venous or pulmonary vessels or in the cardiac ventricles, (2) with radioactivity throughout the entire body compartment and imaged with 3 min static frames and 12 min in list-mode that was reformatted into four 3-min frames, and (3) with radioactivity throughout the body compartment and imaged in list-mode and reformatted into sequential time frames having durations of 3, 10, 20, 30, 50, and 67 s, respectively (i.e., total of 180 s). All measured concentration values were compared against values acquired from static images or against the actual activity concentrations calculated from the calibrated activities dispensed into the phantom corrected for physical decay of (18)F. These analyses demonstrated that the count rate limitation is minimal or negligible as long as there is no more than 370–440 MBq (10−12 mCi) activity entirely within the axial FOV and that list-mode acquisition yields accurate quantitation of activity concentrations over a clinically realistic range of activities. In addition, reformatting a single list-mode acquisition into frames of different durations retains quantitative accuracy with respect to static frame data and compared to the known radionuclide concentration in the phantom. Within these constraints, the list-mode data acquired with the Biograph 16 PET∕CT system are quantitatively accurate for image-based kinetic analysis.